THE VALUE OF THE CORRELATION BETWEEN MILITARY LEADER CHARACTER AND ORGANIZATIONAL CULTURE AS VECTORS FOR INCREASING ORGANIZATIONAL PERFORMANCE - Alexandru-Marius RIZESCU (Management & Marketing)
In this article, I wanted to conduct an exploratory study to demonstrate the importance of the military leader's character and how performance growth is achieved in the military organization. The study seeks to identify whether there is a significant relationship between the interconnections, implications and valences of military leader character related to increasing organizational effectiveness and organizational efficiency, organizational performance, and the significance by which character enhances the valences of the military leader's skills and the military of each military structure. The issue of character is becoming a major requirement and is considered essential to the professional performance of a military leader. Thus, the formation and development of those professionally valuable character traits in association with organisational culture, performance and professional competence is a complex, timely and comprehensive area of organisational concern.